La lodyans haïtienne, ou la parole séditieuse polyphonie narrative et agentivité collective chez Gary Victor et Francis-Joachim Roy - Boraso, Silvia (Ponti/Ponts, 2022)
Stemmed from the Creolophone reality of Haitian plantations, lodyans is a hybrid genre characterized by an explicit conversational dimension and a comedic purpose. In the 20th century, lodyans’s subversive, irreverent tone constituted a threat to the island’s authoritative governments, which explains why it almost disappeared from the literary scene during the American occupation (1915-1934) and the Duvaliers’ dictatorship (1957-1586). Centered on the seditious, even revolutionary aspect of the genre, the first part of this article will focus on its oral and polyphonic features. In particular, we will analyze the ways in which the different narrative strategies partake in creating a sort of democratic storytelling. The second part will then discuss the role rumors play at a diegetic level. Not only they can be considered as the main topic of the majority of the stories, but they also contribute to produce a collective narrative that usually challenges official discourse. The last section will finally examine how lodyans, as a form of historic counter-speech, can be a powerful means through which Haitian communities recover their agency despite dictatorial suppressions. For our analysis, we will concentrate on the works of two famous lodyanseurs who fought against authoritarianism – Gary Victor and Francis-Joachim Roy.